KAJIAN PENDAPATAN NON HALAL DAN DAMPAK PENGGUNAANNYA TERHADAP REPUTASI DAN KEPERCAYAAN NASABAH PERBANKAN SYARIAH - Muchlis, Saiful; Utomo, Husain Soleh (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
This study aims to determine the form of non-halal income and the impact on reputation and customer trust that is found in sharia banking, especially in PT Bank Muamalat Indonesia Makassar branch. This study used qualitative method based on interpretive paradigm with case study approach, to explain the phenomena that occur in the social scope or the scope of the company. Interview and financial statement analysis is used to gather data. The results of this study indicate that the non-halal income in PT Bank Muamalat Indonesia, Makassar Branch is from interest revenue of deposit in the other banks, and it?s derived to the declining of customer trust, then it can affect to the Bank?s reputation.